(-2)50次方+(-2)49次方+(-2)48次方+。+(-2)+1的值

2022-09-23 16:32

謝謝。
2022-09-23 18:17
(-2)^50+(-2)^49+(-2)^48+…+(-2)+1
=2^50-2^49+2^48-2^47+...-2+1,
=2*2^49-2^49+2*2^47-2^47+...-1
=2^49+2^47+...+2+1
設(shè)b=2^49+2^47+...+2+1,
所以4b=2^51+2^49+...+2^3+4,
所以4b-b=2^51+1,
所以3b=2^51+1,
所以b=(2^51+1)/3,
即(-2)^50+(-2)^49+(-2)^48+…+(-2)+1=(2^51+1)/3.
更多回答
(-2)^50+(-2)^49+(-2)^48+…+(-2)+1
=2^50-2^49+2^48-2^47+...-2+1,
=2*2^49-2^49+2*2^47-2^47+...-1
=2^49+2^47+...+2+1
設(shè)b=2^49+2^47+...+2+1,
所以4b=2^51+2^49+...+2^3+4,
所以4b-b=2^51+1,
所以3b=2^51+1,
所以b=(2^51+1)/3,
即(-2)^50+(-2)^49+(-2)^48+…+(-2)+1=(2^51+1)/3
(-2)^50+(-2)^49+(-2)^48+…+(-2)+1
=2^50-2^49+2^48-2^47+...-2+1,
=2^49+2^47+...+2+1
設(shè)a=2^49+2^47+...+2+1,
所以4a=2^51+2^49+...+2^3+4,
所以4a-a=2^51+1,
所以3a=2^51+1,
所以a=(2^51+1)/3,
即(-2)^50+(-2)^49+(-2)^48+…+(-2)+1=(2^51+1)/3.
應(yīng)該是(2^51-1)/3
熱門問答